Integrasi Pendidikan Agama Islam untuk Kompetisi Global: Rekonstruksi Epistemologi, Model Kurikulum, dan Implementasi Profil Pelajar Rahmatan Lil Alamin - Muhammad Nurul Maulida; Sari Hernawati; Nanang Nurcholis (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Amidst the massive globalization and disruption of the Industrial Revolution 4.0 era, Islamic Religious Education (PAI) faces existential challenges not only to preserve religious traditions but also to produce globally competitive human resources. This study aims to formulate a comprehensive PAI integration model, from the epistemological foundation to the practical implementation of the curriculum, in order to shape students who are faithful, have noble character, and master 21st-century competencies. Using library research methods with content analysis of authoritative literature and the latest policies, this study found that the paradigm of the dichotomy of knowledge must be replaced by a paradigm of integration-interconnection. The results show that the "Spider Web" model of M. Amin Abdullah and the "Tree of Knowledge" of Imam Suprayogo offer a solid philosophical framework for uniting religious knowledge and science. At the practical level, leading educational institutions such as MAN Insan Cendekia, International Islamic Boarding School (IIBS), and SMA Trensains have succeeded in developing a hybrid curriculum that synergizes revelation with modern science. Furthermore, the implementation of the Rahmatan Lil Alamin Student Profile (P2RA), integrated with the 4C skills (Critical Thinking, Creativity, Communication, and Collaboration), has proven effective in developing moderate and adaptive character. This article recommends the need for systemic reform in Islamic Religious Education curriculum design to be more responsive to global dynamics without losing spiritual identity.